2014
DOI: 10.1177/216507991406200605
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Personnel's Knowledge of, Attitudes Toward, and Practice to Prevent Needlestick Injuries

Abstract: Anesthesia personnel are at risk for needlestick injuries (NSIs). This study evaluated the knowledge of, attitudes toward, and practice of preventing NSIs among anesthesia personnel in four Iranian university hospitals. A self-administered anonymous questionnaire was distributed to 104 anesthesia personnel. In addition, hospital infection control center records were reviewed. The prevalence of NSI among anesthesia personnel was 56.8%. Only 32.2% reported their NSI. Men were more knowledgeable about the risks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Although a majority of respondents subjectively reported a positive knowledge level for treating a needlestick injury appropriately, only a minority showed sufficient knowledge related to occupational safety about post-exposure prophylaxis of hepatitis B- and C-virus infection and HIV. Other studies in this field also revealed deficits regarding the respective aftercare [37,56,57], finding the same gap between subjective statements and tested knowledge. Interestingly, more respondents reported the sufficient competency of appropriate behaviour in the case of needlestick injuries.…”
Section: Discussionsupporting
confidence: 56%
“…Although a majority of respondents subjectively reported a positive knowledge level for treating a needlestick injury appropriately, only a minority showed sufficient knowledge related to occupational safety about post-exposure prophylaxis of hepatitis B- and C-virus infection and HIV. Other studies in this field also revealed deficits regarding the respective aftercare [37,56,57], finding the same gap between subjective statements and tested knowledge. Interestingly, more respondents reported the sufficient competency of appropriate behaviour in the case of needlestick injuries.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies demonstrated that barriers to complete vaccination included low levels of awareness. [8,22] In addition to failure to receive vaccinations, another reason for nonprotection is nonresponse to HBV vaccinations. [18] Although nonresponders might benefit from revaccination, some healthcare workers did not even know their HBV status.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] In comparison with HIV or HCV, HBV transmission risks from infections to nonimmune individuals through sharp injuries are higher. [8,9]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations